2019
DOI: 10.3856/vol47-issue3-fulltext-17
|View full text |Cite
|
Sign up to set email alerts
|

The effect of astaxanthin and β carotene inclusion in diets for growth, reproduction and pigmentation of the peppermint shrimp Lysmata wurdemanni

Abstract: The effect of the incorporation of three different concentrations (0.5, 1 and 1.5%) of either astaxanthin (A) or β-carotene (B) was evaluated during the feeding of peppermint shrimp Lysmata wurdemanni post-larvae with six isonitrogenous (34%) and isolipidic (8%) diets. Six treatments: A(0.5), A(1), A(1.5), B(0.5), B(1) and B(1.5), and a control group were evaluate with three replicates and five post-larvae (initial weight 0.03 ± 0.007 g) per replicate. After 105 days of culture, the survival, weight gain, numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…This can be attributed to the presence of beta-carotene in both the fermented broth and extract forms of K. marxianus derived 3S, 3’S-AST. Díaz-Jiménez et al found that an increase in the level of β-carotene in the diet can increase the accumulation of astaxanthin in the tissue 42 . They suggested that because the oxidisation of the positions 3, 3ʹ, 4, 4ʹ of β-ionone rings of β-carotene occurs 43 , allowing a gradual increase relative to the dietary concentration, which can be readily integrated into metabolic processes 44 .…”
Section: Discussionmentioning
confidence: 99%
“…This can be attributed to the presence of beta-carotene in both the fermented broth and extract forms of K. marxianus derived 3S, 3’S-AST. Díaz-Jiménez et al found that an increase in the level of β-carotene in the diet can increase the accumulation of astaxanthin in the tissue 42 . They suggested that because the oxidisation of the positions 3, 3ʹ, 4, 4ʹ of β-ionone rings of β-carotene occurs 43 , allowing a gradual increase relative to the dietary concentration, which can be readily integrated into metabolic processes 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Increase the relative percentage of survival following Vibrio harveyi infection Eldessouki et al ( 2022 ) 80 mg kg −1 For 4 weeks Synthetic High-level resistance to white spot syndrome virus (WSSV), is associated with remarkable improvement of hemolymph immunological index, including phagocytic activity, total hemocyte count as well as phenoloxidase, anti-superoxide radical activity, bacteriolytic activity antibacterial activities. AX also promoted mRNA expression of antioxidant enzyme genes (CAT, cMnSOD, and GPx) in the hepatopancreas Salarzadeh and Rajabi ( 2015 ) Kuruma shrimp, Marsupenaeus japonicus 400, 800, 1200 mg kg −1 For 56 days Synthetic AX improved total hemocyte count, viable cells count, and the rate of phagocyte activity of juvenile shrimp Yamada et al ( 1990 ) Asian tiger shrimp, Penaeus monodon 71.5 mg kg −1 For 8 weeks Synthetic Juveniles fed the diet supplemented with AX displayed astounding antioxidant status in stressed shrimp Díaz-Jiménez et al ( 2019 ) 80 mg kg ‒1 For 8 weeks AX exhibited enhanced antioxidant defense capability (SOD) and better hepatopancreatic function (lower hemolymph ALT and AST) Chien et al ( 2003 ) 200–300 mg kg −1 Algal Greater resistance to white spot syndrome virus (WSSV), while phenoloxidase activity and total hemocyte count were negatively correlated Supamattaya et al ( 2005 ) Giant freshwater prawn, Macrobrachium rosenbergii 0.67 and 1.34 nmol g −1 via injection Synthetic Improved survival and resistance against Lactococcus garvieae infection Angeles Jr et al ( 2009 ) …”
Section: Benefits Of Astaxanthin On the Antioxidant Capacity Immunity...mentioning
confidence: 99%
“…Wade et al (2015) found that the weight of juvenile black tiger shrimp was significantly higher when H. pluvialis was included in the diet compared to the control diet (0% microalgae). According to Diaz-Jiménez, Hernandez-Vergara, Pérez-Rostro, and Ortega-Clement (2019), crustaceans select different sources of microalgae based on their food preferences and metabolic requirements. Omnivorous crustaceans may adjust their metabolic activity according to the availability or the quality of the feed.…”
Section: Resultsmentioning
confidence: 99%